2016
DOI: 10.15452/cejnm.2016.07.0024
|View full text |Cite
|
Sign up to set email alerts
|

Datamining techniques - decision tree: new view on nurses' intention to leave

Abstract: Aim: The aim of the survey is to identify factors of the work environment which are important for general nurses when they are considering whether or not to leave their current employer. Design: The research consists of an observational and a crosssectional study. Methods: Based on a modified interpretation of Herzberg's theory, we created a structured interview to investigate environmental factors. Interviewers carried out 1,992 interviews with hospital nurses working in the Czech Republic, between 2011 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…In addition, while recognition was associated with lower nurses’ turnover intention [ 3 , 24 , 33 ], workplace bullying was associated with higher nurses’ turnover intention [ 7 , 28 ]. Vévoda, Vévodová, Bubeníková, Kisvetrová, and Ivanová; and Wubetie et al found that salary is associated with nurses’ turnover intention [ 2 , 44 ]. Furthermore, leadership and supervision support were significantly associated with turnover intention [ 34 , 40 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while recognition was associated with lower nurses’ turnover intention [ 3 , 24 , 33 ], workplace bullying was associated with higher nurses’ turnover intention [ 7 , 28 ]. Vévoda, Vévodová, Bubeníková, Kisvetrová, and Ivanová; and Wubetie et al found that salary is associated with nurses’ turnover intention [ 2 , 44 ]. Furthermore, leadership and supervision support were significantly associated with turnover intention [ 34 , 40 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nurse turnover has been defined as a global healthcare-system issue [ 1 ]. It has been defended as voluntary and early termination of nurses’ employment [ 2 ]. Nurse turnover could be either organizational or professional, with the latter being the most consequential because of its contribution to the preexisting nurse shortage [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dangare and Apte [24] use various data-mining techniques such as decision trees, Naïve Bayes, as well as neural networks to analyze heart disease. Vévoda et al [25] monitored factors in the working environment influencing the decisions of nurses to stay with or leave their employer. The collected data from the questionnaires were analyzed using data-mining tools, decision trees, and non-parametric tests.…”
Section: Use Of Decision Treesmentioning
confidence: 99%
“…Otevřená kultura, ve které mohou být nedostatky, chyby a nežádoucí události diskutovány, může pomoci snížit výskyt pochybení. Jak ukazují některé průzkumy [5,7,20], množství práce při nedostatku kvalifikovaného personálu přispívá ke stresovosti a promítá se na pracovním výkonu.…”
Section: Diskuseunclassified